Next generation science standards assessment for Java coastal students - Sarwi Sarwi; Sigit Saptono; Siti Fathonah; Winarto Winarto (Intelektual Pustaka Media Utama, 2023)
In the 21st-century, we need a generation who can read and face the challenges of the times. The research aimed to master patterns of science with the next generation science standards (NGSS) standards of junior high school students in north coastal areas of Java Island. The research method is quantitative expose-facto and subjects were 228 students determined by purposive sampling. The students who come from Tegal, Pekalongan, Pati and Demak Regencies north coastal Java Island, Indonesia. The results showed a significant difference between the achievement of students in Tegal, Pekalongan, Pati, and Demak Regencies (p=0.012; ∝=0.05). Based on the analysis of variance (ANOVA) test, there was a significant difference between the groups of students’ achievements in mastery of science oriented NGSS. It can be concluded that the achievement among students from four different regions is quite significant. Students from families with middle and upper economic levels have low achievement but students with low economic levels have high academic achievement.